AML-029 Quizartinib Prolonged Overall Survival (OS) vs Placebo Plus Intensive Induction and Consolidation Therapy Followed by Single-Agent Continuation in Patients Aged 18-75 Years With Newly Diagnosed FLT3-Internal Tandem Duplication Positive (FLT3-ITD+) Acute Myeloid Leukemia (AML) - Erba, Harry; Montesinos, Pau; Vrhovac, Radovan; Patkowska, Elzbieta; Kim, Hee-Je; Zak, Pavel; Wang, Po-Nan; Mitov, Tsvetomir; Hanyok, James; Liu, Li; Benzohra, Aziz; Lesegretain, Arnaud; et al. (Clinical lymphoma, myeloma & leukemia, 2022)
OBJECTIVES: Quizartinib is an oral, potent, selective, type II FLT3 inhibitor with prolonged OS as a single-agent in relapsed/refractory FLT3-ITD+ AML. We report results from the global, randomized, double-blind, phase 3 QuANTUM-First trial (NCT02668653), evaluating quizartinib plus standard induction and post-remission consolidation (including allogeneic hematopoietic cell transplant [allo-HCT] in first complete remission [CR1]) followed by single-agent continuation (up to 3 years) vs placebo plus chemotherapy in newly diagnosed FLT3-ITD+ AML. METHODS: Patients 18-75 years with newly diagnosed FLT3-ITD+ AML received induction with cytarabine 100 or 200 mg/m2/day (days 1-7) and daunorubicin 60 mg/m2/day or idarubicin 12 mg/m2/day (days 1-3). Patients were randomized to quizartinib (40 mg/day [days 8-21]) or placebo; stratified by region, age, and white blood cell count at diagnosis. Patients with CR or CR with incomplete hematologic recovery (CRi) received up to 4 cycles of high-dose cytarabine plus quizartinib (40 mg/day) or placebo and/or allo-HCT followed by continuation with quizartinib (30-60 mg/day) or placebo (up to 3 years). The primary endpoint was OS. RESULTS: Between September 2016 and August 2019, 539 patients were randomized (quizartinib [n=268], placebo [n=271]). Median age was 56 years (range, 20-75 years). As of August 2021 (median follow-up, 39.2 months), 58 patients remained on continuation. Median OS was significantly longer with quizartinib vs placebo (31.9 vs 15.1 months; HR, 0.776; 95% CI, 0.615-0.979; 2-sided P=.0324). CR+CRi rates were 71.6% and 64.9%, respectively. Allo-HCT in CR1 was performed in 157 patients (quizartinib, 31%; placebo, 27%). When censored for allo-HCT, OS trended longer with quizartinib vs placebo (HR, 0.752; 95% CI, 0.562-1.008; 2-sided P=.055). Relapse-free survival was longer with quizartinib vs placebo (HR, 0.733; 95% CI, 0.554-0.969). Grade ≥3 adverse events (AEs) were similar across arms. Discontinuations due to AEs occurred in 20.4% (quizartinib) and 8.6% (placebo). Fifty-six patients died from treatment-emergent AEs (quizartinib, 11.3%; placebo, 9.7%); mostly infections. Grade 3/4 electrocardiographic QT prolongation occurred in 3.0% (quizartinib) and 1.1% (placebo). CONCLUSIONS: Quizartinib plus standard therapy, followed by continuation, including after allo-HCT, for up to 3 years was tolerable with statistically significant and clinically meaningful OS improvements in adults ≤75 years with newly diagnosed FLT3-ITD+ AML.
Keywords: dospělí; Leukemia, Myeloid, Acute; Humans; lidé středního věku; Middle Aged; akutní myeloidní leukemie; Hematopoietic Stem Cell Transplantation; Phenylurea Compounds; Idarubicin; Consolidation Chemotherapy; Benzothiazoles; fms-Like Tyrosine Kinase 3; idarubicin; cytarabin; benzothiazoly; transplantace hematopoetických kmenových buněk; Adult; fenylmočovinové sloučeniny; daunomycin; Cytarabine; Daunorubicin; lidé; konsolidační chemoterapie; tyrosinkinasa 3 podobná fms